THE EFFECTIVENESS OF CILOSTAZOL IN PATIENTS WITH GENERALIZED ATHEROSCLEROSIS (World Science, 2020)
The aim of the study is to investigate the effectiveness of cilostazol in patients with generalized atherosclerosis (GAS).A comprehensive examination of 65 male patients with proved GAS was performed (lesions of the lower extremities, carotid, mesenteric, coronary, cerebral arteries) and 28 healthy males (comparison group - CG) aged over 60 years. Patients with GAS consisted of 2 groups: GAS1 - patients in addition to basic therapy received cilostazol (C; 100 mg 2 times per day); GAS2 - placebo. Patients with GAS showed a significant deterioration in blood flow (decrease in its volumetric blood flow - FV, increase in peak systolic velocity - PSV) in all studied arteries, episodes of myocardial ischemia according to daily ECG monitoring, decreased cognitive function (CF). In patients with GAS1 on the background of taking C observed improvement (p